FreeSWITCH Cookbook : over 40 recipes to help you get the most out of your FreeSWITCH server : [quick answers to common problems] - Minessale, Anthony (Packt Pub., 2012)
This is a problem-solution approach to take your FreeSWITCH skills to the next level, where everything is explained in a practical way. If you are a system administrator, hobbyist, or someone who uses FreeSWITCH on a regular basis, this book is for you. Whether you are a FreeSWITCH expert or just getting started, this book will take your skills to the next level.